Prenatal ethanol exposure modifies locomotor activity and induces selective changes in Met-Enkephalin content in adolescent rats - Méndez Ubach, Milagros (2019)
Prenatal ethanol exposure (PEE) facilitates alcohol acceptance and intake, suggesting that ethanol in uteromay increase the probability of drug abuse during adolescence and adulthood. Alcohol reinforcement involves the ethanol-induced activation of opioidergic systems in mesocorticolimbic areas. Changes in opioidneurotransmission may be relevant during ethanol intoxication, as well as in the adaptive neural responsesinduced by the drug. Some studies have assessed the possible changes in opioidergic systems as a functionof ethanol exposure in adolescent animals. However, PEE effects upon locomotive responses elicited by anethanol challenge and modulation of neurotransmission of opioidergic systems remain to be understood. Thiswork assessed the susceptibility of adolescent rats to prenatal and/or postnatal ethanol exposure in terms oflocomotive responses, as well as alcohol-related effects on Methionine-enkephalin (Met-enk) expression inbrain areas related to drug reinforcement. Pregnant rats received a daily intragastric administration of ethanol(2 g/kg) or water, during gestational days 17-20. Adolescents at postnatal day 30 (PD30) were tested in afirst baseline trial (habituation session) and evaluated in terms of spontaneous activity. Thereafter, animalsreceived an ip injection of vehicle (saline 0.9% w/v) (vehicle session) and were immediately evaluated interms of activity during 30 min. After this second trial, animals from both prenatal treatments were injectedwith ethanol (1.0 g/kg ip) or saline, and locomotor activity was immediately assessed for 30 min (drug session). Met-enk content was quantitated by radioimmunoassay in several brain regions: ventral tegmental area[VTA], nucleus accumbens [NAcc], prefrontal cortex [PFC], substantia nigra [SN], caudate-putamen [CP],amygdala, hypothalamus and hippocampus. PEE significantly reduced rearing responses. Ethanol challenge atPD30 decreased horizontal locomotion and showed a tendency to reduce rearings and stereotyped behaviors.PEE increased Met-enk content in the PFC, CP, hypothalamus and hippocampus, but did not alter peptidelevels in the amygdala, VTA and NAcc. These findings suggest that PEE selectively modifies behavioralparameters at PD30 and induces specific changes in Met-enk content in regions of the mesocortical andnigrostriatal pathways, the hypothalamus and hippocampus. Prenatal and postnatal ethanol actions on motoractivity in adolescents could involve activation of specific neural enkephalinergic pathways.